Obstetric fistulae in southern Mozambique: incidence, obstetric characteristics and treatment - Sibone Mocumbi; Claudia Hanson; Ulf Högberg; Helena Boene; Peter von Dadelszen; Anna Bergström; Khátia Munguambe; Esperança Sevene; the CLIP working group (BMC, 2017)
Abstract Background Obstetric fistula is one of the most devastating consequences of unmet needs in obstetric services. Systematic reviews suggest that the pooled incidence of fistulae in community-based studies is 0.09 per 1000 recently pregnant women; however, as facility delivery is increasing, for the most part, in Africa, incidence of fistula should decrease. Few population-based studies on fistulae have been undertaken in Sub-Saharan Africa, including Mozambique. This study aimed to estimate the incidence of obstetric fistulae in recently delivered mothers, and to describe the clinical characteristics and care, as well as the outcome, after surgical repair. Methods We selected women who had delivered up to 12 months before the start of the study (June, 1st 2016). They were part of a cohort of women of reproductive age (12-49 years), recruited from selected clusters in rural areas of Maputo and Gaza provinces, Southern Mozambique, who were participating in an intervention trial (the Community Level Interventions for Pre-eclampsia trial or CLIP trial). Case identification was completed by self-reported constant urine leakage and was confirmed by clinical assessment. Women who had confirmed obstetric fistulae were referred for surgical repair. Data were entered into a REDCap database and analysed using R software. Results Five women with obstetric fistulae were detected among 4358 interviewed, giving an incidence of 1.1 per 1000 recently pregnant women (95% CI 2.16-0.14). All but one had Caesarean section and all of the babies died. Four were stillborn, and one died very soon after birth. All of the patients identified and reached the primary health facility in reasonable time. Delays occurred in the care: in diagnosis of obstructed labour, and in the decision to refer to the secondary or third-level hospital. All but one of the women were referred to surgical repair and the fistulae successfully closed. Conclusion This population-based study reports a high incidence of obstetric fistulae in an area with high numbers of facility births. Few first and second delays in reaching care, but many third delays in receiving care, were identified. This raises concerns for quality of care.